Differentially promoted peripheral nerve regeneration by grafted Schwann cells over-expressing different FGF-2 isoforms - Kirsten Haastert (Neurobiology of Disease, 2006)
Artificial nerve grafts are needed to reconstruct massive defects in the peripheral nervous system when autologous nerve grafts are not available in sufficient amounts. Nerve grafts containing Schwann cells display a suitable substrate for long-distance regeneration. We present here a comprehensive analysis of the in vivo effects of different isoforms of fibroblast growth factor-2 (FGF-2) on peripheral nerve regeneration across long gaps. FGF-2 isoforms were provided by grafted, genetically modified Schwann cells over-expressing 18-kDa-FGF-2 and 21-/23-kDa-FGF-2, respectively. Functional tests evaluated motor and sensory recovery. Additionally, morphometrical analyses of regenerated nerves were performed 3 and 6 months after grafting. Distinct regeneration promoting effects of the different FGF-2 isoforms were found. 18-kDa-FGF-2 mediated inhibitory effects on the grade of myelination of regenerating axons, whereas 21-/23-kDa-FGF-2 mediated early recovery of sensory functions and stimulation of long-distance myelination of regenerating axons. The results contribute to the development of new therapeutic strategies in peripheral nerve repair.